Female work and virtuality in a pandemic in Metropolitan Lima - Benites Medina, Marcela (2024)
The COVID 19 pandemic made visible the structural problems of our society, one of the main ones being the precarious conditions of women’s work, in this sense, the article analyzes the access and use of women from the popular sectors to virtuality to carry out their work activities and communicate with their environment. The study population is made up of 173 working women from 18 to 55 years of age, dependent and independent from the popular sectors of Metropolitan Lima; to capture information on their sociodemographic characteristics, the type of paid and unpaid work, access and use of the Internet, the type of work carried out, and work communication. The information was statistically analyzed using the SPSS. The results indicate that the majority of working women had an Internet connection at home, the cell phone was the most used technological device for work, family and amical communication. Most of the working women are dependent (59.5%), however, there is a significant percentage of independent (40.5%); both worked mainly face-to-face, thus evidencing the high risk of contagion to which working women and their families were exposed.